Available Micronutrient Status in relation to Soil Properties in Some Villages under Four Agro-climatic Features of West Bengal - and G.C. Banik, S.K. Ray (Journal of the Indian Society of Soil Science, 2016)
The deficiency and toxicity range of micronutrients namely, zinc (Zn), iron (Fe), manganese (Mn), copper (Cu), boron (B) etc., in soil is narrow; therefore proper assessment of available micronutrient status in soil is very important. The availability of micronutrients under flood plain alluvial agro-climatic zone of West Bengal, India may be influenced due to the different agro-climatic features (ACF) and also variation in physicochemical properties of the soil, which may ultimately affect the optimum crop yield. With this background, available micronutrient status was assessed in fifty two topsoil (0-20 cm) at four different agro-climatic features (flood prone rainfed, undulated rainfed upland, high flood plain (diara) and flood prone situations) in four different districts (Uttar Dinajpur, Dakshin Dinajpur, Malda and Murshidabad, respectively) of West Bengal. The mean DTPA extractable Fe, Mn, Cu and Zn in these ACF were in the range of 7.11-8.17, 1.50-2.93, 1.04-2.03 and 0.73-0.87 mg kg-1, respectively. The available B was in the range of 0.39-0.49 mg kg-1. Among the soil micronutrients, Zn and B were found deficient by 20 and 60% soil samples, respectively. The correlation matrix of micronutrient status with different soil physicochemical properties showed that Fe, Mn, Cu and B had positive correlations with clay, organic carbon, potassium and CEC, and negative correlations with sand and pH. Zinc was significantly and positively correlated with electrical conductivity. Boron and Mn had positive correlation with soil pH and organic carbon content. Zinc had significant positive correlation with sand and significantly negative relationship with available phosphorus.